Sistem Pendukung Keputusan Pemilihan Supplier Terbaik Menggunakan AHP dan TOPSIS - Ahmad Noval Ramadhan; Nurhasanah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Grocery retail continuity depends strongly on how a store selects suppliers. At Toko Sembako Basuki, assessment is still manual and personal, so ranking trails are hard to re-audit. A web Decision Support System was therefore built by combining Analytical Hierarchy Process (AHP) for criterion weighting and the TOPSIS method for ordering alternatives near an ideal solution. The stack is PHP Native, MySQL, Bootstrap, and TCPDF. Five aspects are scored: price as cost, plus product quality, delivery punctuality, service quality, and payment tenor as benefit. Verification uses Black Box Testing, White Box Testing, manual arithmetic cross check, and User Acceptance Testing. AHP remains consistent (Consistency Ratio 0.0391) and product quality leads with weight 0.5215. TOPSIS puts Supplier Sembako on top (Vi = 1.0000). Hence AHP–TOPSIS reduces subjectivity in supplier selection.